Mulheres na ciência regional: análise da presença na produção científica das docentes e pesquisadoras da Universidade Federal do Pará- UFPA - PINHEIRO, Caroline Corrêa (Universidade Federal do Pará, 2024)
Scientific production is a fundamental instrument to promote and strengthen the knowledge cycle. This contribution to the production of knowledge occurs through the dissemination of articles in journals, indexed in national and international databases, it also contributes to the certification of research and recognition by peers, which guarantees acceptance and visibility in the scientific society. The female presence in the scientific field has contributed to the production of knowledge, enabling social discussions about the reasons that keep them less productive and the impasses in the progression of the scientific career within universities. In this sense, this research sought to analyze the female presence through scientific production and visibility in publications indexed in Scopus. For this, it aimed to identify the scientific production of UFPA researchers at Scopus in the time frame from 2010 to 2021; categorize scientific production and visibility metadata; to map the networks of co-authorship, of co-occurrence of keywords from the scientific production of women at UFPA; present an overview of the female presence at UFPA by thematic areas. This is a research characterized as quantitative-qualitative, exploratory-descriptive and sought to relate variables and indicators that can measure and evaluate the scientific production of UFPA researchers indexed in Scopus, through the search term affiliation "university of paramedics". ”, using bibliometric techniques for research. The collected data were grouped into three quadrennia: a) 2010 to 2013, b) 2014-2017 e) 2018 to 2021. For the elaboration of maps with the co-authorship networks and co-occurrence of keywords, the VOSviewer software was used. There was a gradual increase in publications by researchers in Scopus and a high level of production by teachers and researchers in Biological Sciences and Health Sciences. Finally, it is possible to infer that the female scientific production at UFPA is focused on collective well-being and regional development. In this way, scientific collaboration between women has the potential to impact health and sustainable Amazonian development.